Clinical Course and Impact of Immune Checkpoint Inhibitor Colitis Resembling Microscopic Colitis. Issue 2 (15th March 2022) - Fredrick, Thomas W; Ramos, Guilherme P; Braga Neto, Manuel B; Kane, Sunanda; Faubion, William A; Loftus, Edward V; Pardi, Darrell S; Pasha, Shabana F; Farraye, Francis A; Zhang, Lizhi; Raffals, Laura E
Abstract: Background: Microscopic colitis (MC) is suspected to result from increased immune activity in gut mucosa. Immune checkpoint inhibitors (ICIs) treat cancer by activating the immune system, and further investigation is needed regarding their role in the development of MC. Methods: A retrospective case series investigated cases of endoscopically and histologically confirmed MC developing after administration of ICIs. Clinical notes and medication administration records were reviewed for demographics, symptom duration, and treatment response. Results: Nineteen cases of de novo MC were identified, with 95% of cases requiring steroid treatment, 53% presenting with hospitalization, and colitis-related mortality in 1 individual. Symptom onset occurred a median of 160 days after initiation of ICI therapy and 53 days after their most recent dose of therapy. Patients had a median of 125 days of symptoms, and ICI therapy was held in 70% of individuals due for treatment. Conclusions: MC can develop after ICI administration, and presents with severe symptoms, often requiring hospitalization and steroid treatment. In certain individuals this can require a prolonged treatment course of steroid therapy or immunomodulators. Individuals developing diarrhea after ICI therapy warrant thorough workup including endoscopy and rapid treatment initiation given the disease severity observed in this series. Lay Summary: We describe the development and disease course of microscopic colitis, a previously considered benign disease, arising in patients receiving immune checkpoint inhibitor therapy for cancer. This complication has a prolonged disease duration and frequently results in hospitalization.